PERSONAL SOCIALIZATION AND INSTITUTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the assessment of social norms, values, and expectations that influence people's behavior and decisions, and how family strength depends on the relationships, responsibilities, roles, and gender roles formed through these norms. Social norms vary across national cultures and ethnic traditions, and explore how family life is organized, relationships, and conflict resolution methods differ in each society.